Analisis Determinan Harga Saham Syariah Perusahaan Sektor Barang Konsumsi yang Terdaftar Issi Periode Tahun 2018-2023 - Mohammad Ridwan; Erliyana Saputri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study investigates the influence of leverage, liquidity and company size on the share prices of companies classified as sharia shares, with profitability as a moderating variable. The research object focuses on companies in the consumer goods industry sector listed in the Indonesia Sharia Stock Index (ISSI) in the 2018–2023 period. The research approach uses quantitative methods with panel data regression and Moderated Regression Analysis (MRA) using EViews version 13 to test the relationship between variables. The research results show that leverage and liquidity have no effect on sharia stock prices. On the other hand, company size and profitability have a positive effect on sharia share prices, indicating that company size and good profit performance can increase investor confidence. Profitability is proven to have a role as a moderating variable in the sharia stock price determinant model. The results of the analysis show that profitability weakens the effect of leverage on sharia share prices, indicating that investors are more tolerant of leverage conditions if the company is able to support stable and prospective profitability. Furthermore, profitability is able to strengthen the relationship between the influence of likuiditas and firm size on sharia share prices. These results highlight the importance of considering internal financial factors and company size in shaping investment decisions within the sharia capital market.